2019
DOI: 10.1101/847525
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Antagonistic odor interactions in olfactory sensory neurons are widespread in freely breathing mice

Abstract: Odor landscapes contain complex blends of discrete molecules that each activate unique, overlapping populations of olfactory sensory neurons (OSNs). Despite the presence of hundreds of OSN subtypes in many animals, the overlapping nature of odor inputs may lead to saturation of neural responses at the early stages of stimulus encoding. Information loss due to saturation could be mitigated by normalizing mechanisms such as antagonism at the level of receptor-ligand interactions, whose existence and prevalence r… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 60 publications
1
16
0
Order By: Relevance
“…A two-dimensional retinal pattern includes multiple objects of potential interest, occluding one another and perhaps in motion, embedded within regions that may exhibit very different intensities of light and contrast. Odorant receptors are affected by concentration as well as quality; moreover, the ligands that comprise different sources of interest may compete for the same receptors—as agonists, partial agonists, or antagonists—and hence occlude source-specific signal patterns (Gronowitz et al, 2020 ; Xu et al, 2020 ; Zak et al, 2020 ). Indeed, even two source odorants in binary mixtures often strongly interfere with one another, generating activation patterns that do not resemble the diagnostic patterns of any individual source (Linster and Cleland, 2004 ; Riffell, 2012 ; Thomas-Danguin et al, 2014 ).…”
Section: Three Core Problems In Engineering Sensory Systemsmentioning
confidence: 99%
“…A two-dimensional retinal pattern includes multiple objects of potential interest, occluding one another and perhaps in motion, embedded within regions that may exhibit very different intensities of light and contrast. Odorant receptors are affected by concentration as well as quality; moreover, the ligands that comprise different sources of interest may compete for the same receptors—as agonists, partial agonists, or antagonists—and hence occlude source-specific signal patterns (Gronowitz et al, 2020 ; Xu et al, 2020 ; Zak et al, 2020 ). Indeed, even two source odorants in binary mixtures often strongly interfere with one another, generating activation patterns that do not resemble the diagnostic patterns of any individual source (Linster and Cleland, 2004 ; Riffell, 2012 ; Thomas-Danguin et al, 2014 ).…”
Section: Three Core Problems In Engineering Sensory Systemsmentioning
confidence: 99%
“…Several mechanisms may contribute to the sublinear summation of odorant responses. These include interactions between odorants at the olfactory epithelium (Kurahashi et al, 1994;Duchamp-Viret et al, 2003;Oka et al, 2004;Grossman et al, 2008;Takeuchi et al, 2009;Reddy et al, 2018;Xu et al, 2019;Zak et al, 2019), processing in the olfactory bulb (Giraudet et al, 2002;Linster and Cleland, 2004;Tabor et al, 2004;Lin et al, 2006), and further normalization within piriform cortex, implemented by local inhibition. Inhibitory circuits within the piriform cortex have indeed been shown to play a major role in shaping piriform representations Isaacson, 2009, 2011;Franks et al, 2011;Bolding and Franks, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported sublinear mixture responses in olfactory cortex, thereby limiting the possible response space, however, they have not provided models to predict mixture responses (Lei et al, 2006;Yoshida and Mori, 2007;Stettler and Axel, 2009). Sublinearlity of mixture responses is probably inherited to some extent from the olfactory epithelium (Kurahashi et al, 1994;Duchamp-Viret et al, 2003;Oka et al, 2004;Takeuchi et al, 2009;Xu et al, 2020;Zak et al, 2020), as well as from the olfactory bulb where cross odorant inhibition may contribute (Yokoi et al, 1995;Urban, 2002;Aungst et al, 2003;McGann et al, 2005;Arevian et al, 2008;Fantana et al, 2008). The piriform cortex integrates these non-linear odor representations from the olfactory bulb and utilizes local recurrent circuitry to generate representations that presumably support segmentation Isaacson, 2009, 2011;Franks et al, 2011;Miura et al, 2012;Suzuki and Bekkers, 2012;Roland et al, 2017;Bolding and Franks, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Several mechanisms may contribute to the sublinear summation of odorant responses. These include interactions between odorants at the olfactory epithelium (Kurahashi et al, 1994;Duchamp-Viret et al, 2003;Oka et al, 2004;Grossman et al, 2008;Takeuchi et al, 2009;Reddy et al, 2018;Xu et al, 2019;Zak et al, 2019), processing in the olfactory bulb (Giraudet et al, 2002;Linster and Cleland, 2004;Tabor et al, 2004;Lin et al, 2006), and further normalization within piriform cortex, implemented by local inhibition. Inhibitory circuits within the piriform cortex have indeed been shown to play a major role in shaping piriform representations Isaacson, 2009, 2011;Franks et al, 2011;Bolding and Franks, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported sublinear mixture responses in olfactory cortex, thereby limiting the possible response space, however they have not provided models to predict mixture responses (Lei et al, 2006;Yoshida and Mori, 2007;Stettler and Axel, 2009). Sublinearlity of mixture responses is probably inherited to some extent from the olfactory epithelium (Kurahashi et al, 1994;Duchamp-Viret et al, 2003;Oka et al, 2004;Takeuchi et al, 2009;Xu et al, 2020;Zak et al, 2020), as well as from the olfactory bulb where cross odorant inhibition may contribute (Yokoi et al, 1995;Urban, 2002;Aungst et al, 2003;McGann et al, 2005;Arevian et al, 2008;Fantana et al, 2008). The piriform cortex integrates these non-linear odor representations from the olfactory bulb and utilizes local recurrent circuitry to generate representations that presumably support segmentation Isaacson, 2009, 2011;Franks et al, 2011;Miura et al, 2012;Suzuki and Bekkers, 2012;Roland et al, 2017;Bolding and Franks, 2018).…”
Section: Introductionmentioning
confidence: 99%